PENENTUAN WAKTU BAKU ELEMEN KERJA PADA PROSES PERAWATAN CONTINUOUS VARIABLE TRANSMISSION DENGAN METODE TIME AND MOTION STUDY DI BENGKEL MOTOR - Imanuel, Victor; Sukania, I Wayan; Utama, Didi Widya (Universitas Tarumanagara, 2025)
As the number of motor vehicles in Indonesia increases, the demand for vehicle maintenance and repair services also rises. One of the businesses that provide motor vehicle maintenance services is a motorcycle workshop. XYZ Workshop is an MSME (Micro, Small, and Medium Enterprise) engaged in the repair services of motor vehicles and the sale of spare parts, established in 2022. Since its operation, XYZ Workshop has provided various types of motor vehicle maintenance and repair services, starting from inspections, oil changes, wheel tire replacements, and handling CVT (Continuous Variable Transmission) on automatic motorcycles. This research is conducted with the aim of obtaining the standard time for the maintenance activities of Continuous Variable Transmission and understanding the time weight of each work element, from the largest to the smallest. This research uses the time and motion study method to analyze the work elements performed by workers and measure the work time for each element. Based on the calculated standard time for the work elements, the element with the highest standard time is the reassembly movement of the Secondary Sheave with a standard time of 41.901 seconds, while the element with the smallest standard time is the movement of picking up the cover bolts with a standard time of 1.178 seconds. The addition of tools or the design of a working system can be implemented to reduce the standard time of the work element with the highest time, making it faster and reducing the worker’s load.